A delicate balance between rejection and BK polyomavirus associated nephropathy; A retrospective cohort study in renal transplant recipients. - Lilli Gard; Willem van Doesum; Hubert G M Niesters; Willem J van Son; Arjan Diepstra; Coen A Stegeman; Henk Groen; Annelies Riezebos-Brilman; Jan Stephan Sanders (PLoS ONE)
Background The immunosuppressive agents mycophenolate acid (MPA) and tacrolimus (Tac) are associated with a higher incidence of BK polyomavirus nephropathy (BKPyVAN). In this observational retrospective cohort study, the frequency of BK polyomavirus (BKPyV) complications over a 24-month period was studied. Methods 358 renal transplant recipients (RTR) treated with MPA, with either cyclosporine A (CsA) (CsAM group) or Tac (TacM group) and mostly prednisolone, were included. Results Incidence of BKPyV-viremia was not significantly different between the CsAM (n = 42/191) (22.0%) and the TacM (n = 36/167) (21.6%) group. Biopsy proven BKPyVAN occurred more often in the TacM group (6.6%) versus the CsAM group (2.1%) (p = 0.03). Longitudinal data analysis showed a significant earlier decline of viral load in plasma in the CsAM group compared to the TacM group (p = 0.005). The incidence of biopsy proven acute rejection (BPAR) was significantly higher in the CsAM (19.9%) compared to the TacM (10.8%) (p = 0.02) group. Graft loss, estimated glomerular filtration rate and mortality rate did not differ in both treatment groups. Conclusion In conclusion, this study shows that immunosuppressive treatment with Tac and MPA compared to CsA and MPA is associated with a lower incidence of BPAR, but at the cost of an increased risk of developing BKPyVAN in the first two years post-transplant.